Planning for bunkering operations in ocean fishing - Lim, Peter Ah Teck. (2008)
In this dissertation, the bunkering evolutions from an early emphasis on bunkering procedure to recent consideration for environment protection are discussed. The importance to achieve the US Coast Guard standard is reviewed in details together with the ocean bunkering operationThe discussion of the various tonnage of fishing vessels floating in the ocean and their bunker consumption are presented.